The association of in-hospital major bleeding with short-, intermediate-, and long-term mortality among older patients with non-ST-segment elevation myocardial infarction - Lopes, Renato D. (Oxford University Press, 2012)
AIMS: Bleeding complications have been associated with short-term mortality in patients with non-ST-segment elevation myocardial infarction (NSTEMI). Their association with long-term outcomes is less clear. This study examines mortality associated with in-hospital bleeding during NSTEMI over time intervals starting from hospital discharge and extending past 3 years. METHODS AND RESULTS: We studied 32 895 NSTEMI patients aged ≥65 years, using patient-level data from the CRUSADE registry linked with Medicare claims data. We assessed the association of in-hospital major bleeding with short (30 days), intermediate (1 year), and long-term (3 years) mortality among hospital survivors overall, as well as in those patients treated with or without a percutaneous coronary intervention (PCI). We calculated adjusted hazard ratios (HRs) for mortality for bleeders vs. non-bleeders over time intervals from: (i) discharge to 30 days; (ii) 31 days to 1 year; (iii) 1 year to 3 years; and (iv) beyond 3 years. Overall, 11.9% (n = 3902) had an in-hospital major bleeding event. Cumulative mortality was higher in those who had a major bleed vs. those without at 30 days, 1 year, and 3 years. Even after adjustment, major bleeding continued to be significantly associated with higher mortality over time in the overall population: (i) discharge to 30 days [adjusted HR 1.33; 95% confidence interval (CI) 1.18–1.51]; (ii) 31 days to 1 year (1.19; 95% CI 1.10–1.29); (iii) 1 year to 3 years (1.09; 95% CI 1.01–1.18), and (iv) attenuating beyond 3 years (1.14; 95% CI 0.99–1.31). In-hospital bleeding among patients treated with PCI continued to be significantly associated with higher adjusted mortality even beyond 3 years (1.25; 95% CI 1.01–1.54). CONCLUSION: In-hospital major bleeding is associated with short-, intermediate-, and long-term mortality among older patients hospitalized for NSTEMI—this association is strongest within the first 30 days, but remains significant long term, particularly among PCI-treated patients. Despite a probable early hazard related to bleeding, the longer duration of risk in patients who bleed casts doubt on its causal relationship with long-term mortality. Rather, major bleeding likely identifies patients with an underlying risk for mortality.